39.1k views
5 votes
Solve for B: AB + 3C = D

User Thehhv
by
5.6k points

1 Answer

7 votes

If we want to get B by itself, we need to "undo" every operation being done to it. Those operations are (in order):

  • Multiplication by A
  • Addition with 3C

To undo these then, we'll need to:

  • Subtract 3C
  • Divide by A

And, since this is an equation, we'll need to do both of those to the right side as well to keep everything equal. Here we go:

AB + 3C - 3C = D - 3C (subtracting 3C)

AB/A = (D - 3C)/A (dividing by A)

B = (D - 3C)/A

And we're done! If you'd like to see it formatted a little nicer, here's this:


B=(D-3C)/(A)

User Eduardo Santa
by
5.2k points